2020
DOI: 10.3390/nursrep10020023
|View full text |Cite
|
Sign up to set email alerts
|

Blessings and Curses: Exploring the Experiences of New Mothers during the COVID-19 Pandemic

Abstract: The aim of this study was to explore the postpartum experiences of new parents during the COVID-19 pandemic. The postpartum period can be a time of significant transition, both positive and negative, for parents as they navigate new relationships with their babies and shifts in family dynamics. Physical distancing requirements mandated by public health orders during the COVID-19 pandemic had the potential to create even more stress for parents with a newborn. Examining personal experiences would provide health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 41 publications
3
43
0
1
Order By: Relevance
“…The COVID-19 environment also impacted resettled refugee women’s mental health during the postnatal period, causing increased feelings of fear, isolation, and disappointment. These findings are consistent with other recent reports on the experiences of non-newcomer women who are postpartum during COVID-19 in Atlantic Canada [ 14 , 16 , 19 ]. The COVID-specific experiences of non-newcomer women parallels the pre-pandemic postpartum experiences of resettled refugee women.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The COVID-19 environment also impacted resettled refugee women’s mental health during the postnatal period, causing increased feelings of fear, isolation, and disappointment. These findings are consistent with other recent reports on the experiences of non-newcomer women who are postpartum during COVID-19 in Atlantic Canada [ 14 , 16 , 19 ]. The COVID-specific experiences of non-newcomer women parallels the pre-pandemic postpartum experiences of resettled refugee women.…”
Section: Discussionsupporting
confidence: 93%
“…Women in our study described the stresses and pressures they faced as a result of decreased informal support, increased childcare and homeschooling demands, and the closures/restrictions of valuable support services (e.g., doulas)—all of which have been reported in other literature with non-newcomer women [ 10 , 14 , 19 ]. These stressors were coupled with feelings of disappointment and loss related to missed or robbed birth- and postnatal-related moments and milestones [ 14 , 16 , 19 ]. Studies with non-newcomer women have also found significant increases in postpartum anxiety [ 12 ] and depression symptoms [ 61 ] during the pandemic, in addition to a significant increase in healthcare visits for postpartum mental health concerns [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though there were many reported negative impacts of the COVID-19 pandemic, participants also reported unanticipated positive experiences, including less pressure and more time with their baby, which has been reported by others. Like those in our study, Nova Scotian caregivers who responded to an open-ended survey on post-partum experiences during the COVID-19 pandemic also described a complex time, reporting not only negative themes, such as isolation, but also 'blessings', such as freedom from social expectations and more family bonding time (Joy et al, 2020).…”
Section: Changes To Infant Feeding Due To Covid-19mentioning
confidence: 55%